ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TENGAH - Puspita, Shafa Nanda; Maryani, Sri; Purwantho, Herry (Universitas Jenderal Soedirman, 2021)
ABSTRACT. Labor absorption is an important factor in supporting economic development through national income. The low level of employment is still a problem in various regions in Indonesia, especially in Central Java Province. The problem of employment, can be overcome by maximizing the factors that affect the increase in labor absorption. Therefore, it is necessary to analyze the factors that are thought to affect the increase in labor absorption. This study aims to analyze the factors that influence labor absorption in Central Java Province. This study uses a descriptive quantitative approach with a panel data regression model. The best model selection test used is the Chow test, Hausman test, and Lagrange Multiplier test (LM) Test which was carried out using the Eviews 9 software. This study uses cross section data from 35 districts/cities in Central Java Province and time series data on the number of workers, labor force, unemployment, minimum wages, and GRDP of each district/city for the 2015-2020 period. The results of the discussion show that simultaneously and partially the number of workers, the number of the workforce, the number of unemployed, the minimum wage, and GRDP have an effect on the absorption of labor in Central Java Province.Keywords: absorption of labor, panel data, regression. ABSTRAK. Penyerapan tenaga kerja merupakan salah satu faktor penting dalam mendukung pembangunan ekonomi melalui pendapatan nasional. Rendahnya tingkat penyerapan tenaga kerja masih menjadi permasalahan di berbagai daerah di Indonesia khususnya di Provinsi Jawa Tengah. Masalah penyerapan tenaga kerja, dapat diatasi dengan memaksimalkan faktor-faktor yang mempengaruhi peningkatan penyerapan tenaga kerja. Oleh karena itu, perlu dianalisis faktor-faktor yang diduga mempengaruhi peningkatan penyerapan tenaga kerja. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi penyerapan tenaga kerja di Provinsi Jawa Tengah. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan model regresi data panel. Uji pemilihan model terbaik yang digunakan adalah uji Chow, uji Hausman, dan uji Lagrange Multiplier (LM Test) yang dilakukan menggunakan software Eviews 9. Penelitian ini menggunakan data cross section dari 35 kabupaten/kota di Provinsi Jawa Tengah dan data time series jumlah tenaga kerja, angkatan kerja, pengangguran, upah minimum, dan PDRB masing-masing kabupaten/kota periode 2015-2020. Hasil pembahasan menunjukkan bahwa secara simultan dan parsial jumlah tenaga kerja, jumlah angkatan kerja, jumlah pengangguran, upah minimum, dan PDRB berpengaruh terhadap penyerapan tenaga kerja di Provinsi Jawa Tengah.Kata Kunci: data panel, penyerapan tenaga kerja, regresi.